Contact with HIV prevention services highest in gay and bisexual men at greatest risk: cross-sectional survey in Scotland - Hart Graham J; McDaid Lisa M (BMC, 2010)
Abstract Background Men who have sex with men (MSM) remain the group most at risk of acquiring HIV in the UK and new HIV prevention strategies are needed. In this paper, we examine what contact MSM currently have with HIV prevention activities and assess the extent to which these could be utilised further. Methods Anonymous, self-complete questionnaires and Orasure™ oral fluid collection kits were distributed to men visiting the commercial gay scenes in Glasgow and Edinburgh in April/May 2008. 1508 men completed questionnaires (70.5% response rate) and 1277 provided oral fluid samples (59.7% response rate); 1318 men were eligible for inclusion in the analyses. Results 82.5% reported some contact with HIV prevention activities in the past 12 months, 73.1% obtained free condoms from a gay venue or the Internet, 51.1% reported accessing sexual health information (from either leaflets in gay venues or via the Internet), 13.5% reported talking to an outreach worker and 8.0% reported participating in counselling on sexual health or HIV prevention. Contact with HIV prevention activities was associated with frequency of gay scene use and either HIV or other STI testing in the past 12 months, but not with sexual risk behaviours. Utilising counselling was also more likely among men who reported having had an STI in the past 12 months and HIV-positive men. Conclusions Men at highest risk, and those likely to be in contact with sexual health services, are those who report most contact with a range of current HIV prevention activities. Offering combination prevention, including outreach by peer health workers, increased uptake of sexual health services delivering behavioural and biomedical interventions, and supported by social marketing to ensure continued community engagement and support, could be the way forward. Focused investment in the needs of those at highest risk, including those diagnosed HIV-positive, may generate a prevention dividend in the long term.